User Acceptance Analysis of Smart Factory System Implementation Through the Integration of the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) Using SEM-PLS - Sulistyawati Sulistyawati; Feby Artwodini Muqtadiroh (Universitas Ibn Khladun Bogor, 2026)
The rapid advancement of technology in the Industry 4.0 era has encouraged manufacturing companies to undergo digital transformation toward Smart Factory systems. A Smart Factory is a manufacturing system that integrates advanced technologies, data, and automation to create more efficient, precise, and intelligent production processes. However, the successful implementation of a Smart Factory depends not only on the readiness of technological infrastructure but also on users' acceptance and actual usage behavior toward the system. This study aims to analyze the factors influencing user acceptance and actual use of a Smart Factory system in a railway manufacturing company. The research integrates two widely recognized theoretical frameworks, namely the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). The integrated model is employed to examine the relationships among perceived ease of use, perceived usefulness, performance expectancy, effort expectancy, social influence, and facilitating conditions, as well as their effects on behavioral intention and actual system use. This study adopts a quantitative explanatory research design. Data were collected exclusively through a structured questionnaire. All research variables were measured using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both the measurement model and the structural relationships among the constructs.